2023
DOI: 10.1115/1.4056512
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Investigation of High Load Turbine Blade Tip Cavity Structures

Abstract: Leakage flow losses are an important factor affecting turbine aerodynamic efficiency. In this paper, experimental and numerical computational studies are used to target three different tips of highly loaded turbine rotor. The single cavity tip formed by squealers is considered as the original cavity tip structure, and based on this, two structures were improved, cavity winglet tip and double cavity combined winglet tip. Five-hole probe and oil flow visualization are used for experimental studies; numerical cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Chen [12] investigated the aerodynamic performance of three different cavity tip configurations through wind tunnel experiments, including inline squealer, cavity winglet tip and dual−cavity combined winglet tip configurations. Finally, it was found that the dual−cavity combined winglet tip had the best aerodynamic performance, optimizing the aerodynamic performance by 4% compared to the inline squealer structure, while the cavity winglet tip carried out an optimization of 1%.…”
Section: Introductionmentioning
confidence: 99%
“…Chen [12] investigated the aerodynamic performance of three different cavity tip configurations through wind tunnel experiments, including inline squealer, cavity winglet tip and dual−cavity combined winglet tip configurations. Finally, it was found that the dual−cavity combined winglet tip had the best aerodynamic performance, optimizing the aerodynamic performance by 4% compared to the inline squealer structure, while the cavity winglet tip carried out an optimization of 1%.…”
Section: Introductionmentioning
confidence: 99%